Haematopoietic stem cells derived from sheep and human amniotic fluid engraft after transplantation. (18th April 2012) - Shaw, SW; David, AL; Blundell, M; Howe, S; Pipino, C; Maghsoudlou, P; Lee, KH; Atala, A; Porada, CD; Thrasher, A; De Coppi, P
Abstract : Introduction: Mouse amniotic fluid c-Kit(+)/Lin(-) stem (AFS) cells display hematopoietic potential. We explored the haematopoietic potential of sheep and human AFS cells after in utero stem cell transplantation. Methods: Human AFS cells (hAFSC) were isolated from women undergoing 3rd trimester amniodrainage. Sheep AFS cells (sAFSC) were collected under ultrasound guidance (59.5±4.5days, term=145days), and isolated using a sheep-specific CD34 antibody. hAFSC were transplanted into the peritoneal cavity of fetal mice from CD1 mothers (14dpc, n=6). The peripheral blood of recipient mice was analysed 4 weeks postnatal for engraftment by flow-cytometry using anti-human beta2-microglobin antibody. Neonatal tissues collected at 6 weeks were analysed by PCR and immuno-staining for anti-human mitochondrial antibody; bone marrow (BM) was assayed for colony-forming cells. sAFSC were transduced overnight using a lentivirus vector (HIV-SFFV-eGFP, MOI=50) and injected either intravenously into NOD-SCID-gamma (NSG) mice (3x10∧5, N=4 per group) or by ultrasound-guided peritoneal injection back into donor sheep fetuses (n=7; 2x10∧4 sAFSC). Results: hAFS cells were detectable in the peripheral blood, liver, spleen and BM of neonatal mice at 6 weeks postnatal; harvested BM generated colonies of human origin. GFP+ve cells were detected in the peripheral blood, spleen, liver, and BM of NSG mice 3 months after transplantation of transduced sAFSC. Five lambs injected with autologous transduced GFP+CD34+ cells survived to birth (71.4%); peripheral blood of all lambs contained GFP+ cells (1.9-3.8%) maintained at 6 months postnatal. GFP+ cells were detected in the liver and BM of lambs. Conclusion: AFSC have haematopoietic potential and be useful for autologous transplantation.